Pedagogical Strategies Employed by Teachers in Township Schools for Teaching Meiosis and Genetics with Improvised Resources - Ramaila, Sam; Zondi, Syamthanda Mpilwenhle; Mavuru, Lydia (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2025)
This study explored the pedagogical strategies employed by grade 12, life-sciences teachers in township schools to teach complex concepts, such as genetics and meiosis, using improvised teaching resources. Resource constraints in South African township schools often limit learners’ access to traditional teaching materials and technologies. In response, this research examined how teachers adapt and innovate their methods to effectively convey abstract life-sciences concepts. An embedded mixed-methods design was utilized, with a purposive sample of four life-sciences teachers from diverse township schools, selected to reflect varied teaching experiences and resource availability. Data was collected through interviews and classroom observations, offering insights into their instructional practices. Thematic analysis of interview data and systematic observation of classroom activities revealed a range of creative and adaptive pedagogical approaches. Instructors commonly adopted collaborative, learner-centred, and inquiry-based teaching methods. They employed creative strategies, including designing hands-on activities, using analogies, and incorporating real-life examples to enhance learners’ understanding. Collaboration among teachers and the use of community resources also emerged as key strategies for enriching the learning experience. The findings underscore the resilience and ingenuity of grade 12, life-sciences teachers in overcoming resource constraints to create effective educational environments. This study contributes to the understanding of the interplay between pedagogy and resource availability in underserved educational settings, providing valuable insights for educators, policymakers, and curriculum developers aiming to enhance science education in resource-limited contexts.